Ionic Liquid Surface Treatment of Calcite for Improved Compatibility with Polyolefin Matrix - Croitoru, Catalin; Roata, Ionut Claudiu; Pascu, Alexandru; Stanciu, Elena Manuela (IOP Publishing, 2017)
Preliminary surface treatment of crystalline marble powder filler with a dominatingly hydrophobic ionic liquid, namely triethylsulfonium-bis(trifluoromethylsulfonyl) imide has been employed to design a filler with improved compatibility towards non-polar polymer matrices, such as polyolefins. The maximum uptake of ionic liquid per 1g of marble powder was 132 mg. The surface coating of the crystalline phases has been proved by XRD and FTIR spectroscopy, making our method useful in designing fillers with improved dispersibility/ compatibility in/with polyolefins. The floating test method has proved the efficiency of the alkylsulfonium ionic liquid in hydrophobization of the crystalline calcite-rich phase, thus proving useful in obtaining composites with improved properties.